A Comparative Study of Meshtype Retrofitting for Unreinforced Masonry Under In-plane Loading - Sathiparan, N.; Nissanka, N.A.A.C.; Priyankara, R.L.S. (My University, 2016)
Seismic loads directed toward vulnerable masonry structures may cause considerable damage and loss of life. As a result, there is now a desire to increase the seismic resistance of many types of existing masonry structures. Different conventional retrofitting techniques are available to increase the strength and/or ductility of unreinforced masonry walls. Recent years, several researches work on meshtype retrofitting for masonry structures to delay or prevent the collapse of buildings and reduce the number of lives lost during devastating earthquake events. The meshtype retrofitting can be made of any ductile material, including: steel cage, polymer, polypropylene band and plastic carrier bag. In this campaign, six brick masonry wall panels were tested. This was done by applying static horizontal loads on top, combined with a pre-compression level, to obtain information about the failure mode, displacement capacity and strength capacity.
Keywords: Masonry; Earthquake